Interplay of normative beliefs and behavior in developmental patterns of physical and relational aggression in adolescence: a four-wave longitudinal study - Krahé, Barbara; Busching, Robert (Frontiers in Psychology, 2014)
A longitudinal study with N = 1,854 adolescents from Germany investigated patterns of change and gender differences in physical and relational aggression in relation to normative beliefs about aggression. Participants, whose mean age was 13 years at T1, completed self-report measures of physically and relationally aggressive behavior and indicated their normative approval about both forms of aggression at four data waves separated by 12-month intervals. Boys scored higher than did girls on both forms of aggression, but the gender difference was more pronounced for physical aggression. Physical aggression decreased and relational aggression increased over the four data waves in both gender groups. The normative acceptance of both forms of aggression decreased over time, with a greater decrease for the approval of physical aggression. In both gender groups, normative approval of relational aggression prospectively predicted relational aggression across all data waves, and the normative approval of physical aggression predicted physically aggressive behavior at the second and third data waves. A reciprocal reinforcement of aggressive norms and behavior was found for both forms of aggression. The findings are discussed as supporting a social information processing perspective on developmental patterns of change in physical and relational aggression in adolescence.